Contextualisation of Direct Instruction Method in Teaching Reading Comprehension Skills: The Literature Review - Nuraeni Nuraeni; Sitti Aisyah (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2022)
Direct Instruction is an approach where a teacher becomes the center of the teaching process. This teaching strategy is suitable to teach reading comprehension skills. In the process of using the Direct Instruction, a teacher needs to apply three basic concepts those are delivery, design, and documentation which means the teacher must prepare a creative lesson plan that can support students to adapt to a new concept during the ongoing process, the teacher must monitor students’ development using assessment. Some studies show that this method is effective by combining strategies or media and it can improve students’ skills. However, criticisms also hit this method. Some scholar proves from their study that this method is not always effective and is used only for students with low-level knowledge. Keywords: Direct Instruction, Reading Skills, Reading Comprehension